Skeletal function and form : - Carter, Dennis R. (Cambridge University Press, 2001)
Stating their objective as the presentation of "a consistent approach for understanding the role of mechanical factors in skeletal development, growth, maintenance, functional adaptation, and aging," Carter (mechanical engineering, Stanford U.) and Beaupr (Palo Alto VA Rehabilitation Research and Development Center) discuss musculoskeletal form and function within a framework that follows the chronological stages of skeletal ontogeny from the initial formation of joints and bone in the fetus through the life cycle. Much of the engineering analysis behind the development of their theory has been removed from the main body of the text.